Two Cases of Contact Anterior Cruciate Ligament Rupture Combined with a Posterolateral Tibial Plateau Fracture - Liangjun Jiang; Haobo Wu; Shigui Yan (Case Reports in Orthopedics)
Background. The combined occurrence of ACL rupture with a posterolateral tibial plateau fracture has not yet been reported. Two cases of such injuries have been treated in our department for the past three years. Findings. The two patients both suffered injuries from traffic accidents. The radiological examinations showed a ruptured ACL with fracture of the posterolateral tibial plateau. Reconstruction of the ACL was performed via a standard anatomical single bundle ACL reconstruction technique with autologous tendon by arthroscopy. A posterolateral tibia plateau approach was used to reduce and fix the fractured area with the aid of lag screws. After a one-year follow-up, the two patients recovered well and physical examinations showed full knee range of motion with no evidence of ACL instability. Conclusions. The cause of this type injury of ACL rupture with a posterolateral tibial plateau fracture was thought to be by a violent internal tibial rotation/anterior tibial translation without any valgus or varus knee force mechanism during the accident. Satisfactory clinical results were achieved with a standard anatomical single bundle ACL reconstruction by arthroscopy and ORIF for the posterolateral plateau fracture. Both patients reported excellent knee function and fracture healing.